Large-scale and significant expression from pseudogenes in Sodalis glossinidius – a facultative bacterial endosymbiont. Issue 1 (10th January 2020) - Goodhead, Ian; Blow, Frances; Brownridge, Philip; Hughes, Margaret; Kenny, John; Krishna, Ritesh; McLean, Lynn; Pongchaikul, Pisut; Beynon, Rob; Darby, Alistair C.
Abstract : The majority of bacterial genomes have high coding efficiencies, but there are some genomes of intracellular bacteria that have low gene density. The genome of the endosymbiont Sodalis glossinidius contains almost 50 % pseudogenes containing mutations that putatively silence them at the genomic level. We have applied multiple 'omic' strategies, combining Illumina and Pacific Biosciences Single-Molecule Real-Time DNA sequencing and annotation, stranded RNA sequencing and proteome analysis to better understand the transcriptional and translational landscape of Sodalis pseudogenes, and potential mechanisms for their control. Between 53 and 74 % of the Sodalis transcriptome remains active in cell-free culture. The mean sense transcription from coding domain sequences (CDSs) is four times greater than that from pseudogenes. Comparative genomic analysis of six Illumina-sequenced Sodalis isolates from different host Glossina species shows pseudogenes make up ~40 % of the 2729 genes in the core genome, suggesting that they are stable and/or that Sodalis is a recent introduction across the genus Glossina as a facultative symbiont. These data shed further light on the importance of transcriptional and translational control in deciphering host–microbe interactions. The combination of genomics, transcriptomics and proteomics gives a multidimensional perspective for studying prokaryotic genomes with a view to elucidating evolutionary adaptation to novel environmental niches.